2015
DOI: 10.1097/aud.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Channel Envelope Synchrony on Interaural Time Difference Sensitivity in Bilateral Cochlear Implant Listeners

Abstract: While the binaural system was resilient to small delays between envelopes, larger delays significantly deceased ITD sensitivity, both for adjacent and further spaced electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…The results also showed that the range of lateralization with multi-electrode stimulation was typically on par with that of the largest single-electrode lateralization range. This result is consistent with previous literature that showed that ITD sensitivity was also comparable between single-and multi-electrode stimulation (Egger et al, 2016;Francart et al, 2015;Ihlefeld et al, 2014;. In addition, a comparison of different multi-electrode configurations showed that confining the ITD information to the apical end of the electrode array appears to reduce the lateral range of the auditory object.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results also showed that the range of lateralization with multi-electrode stimulation was typically on par with that of the largest single-electrode lateralization range. This result is consistent with previous literature that showed that ITD sensitivity was also comparable between single-and multi-electrode stimulation (Egger et al, 2016;Francart et al, 2015;Ihlefeld et al, 2014;. In addition, a comparison of different multi-electrode configurations showed that confining the ITD information to the apical end of the electrode array appears to reduce the lateral range of the auditory object.…”
Section: Discussionsupporting
confidence: 82%
“…To date, all studies examining ITD sensitivity with multiple electrode stimulation have measured acuity to ITDs, and have shown that ITD discrimination performance does not appear to be significantly poorer than when stimulating on singleelectrode pairs alone (Egger et al, 2016;Francart et al, 2015;Ihlefeld et al, 2014;. However, feasibility and success with multi-electrode ITD stimulation can only really be determined by understanding how ITDs presented on multiple electrodes are perceived by a listener.…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of literature showing that CI listeners are most sensitive to ecologically relevant ITD cues when stimulating with a single, pitch-matched, interaural electrode pair by the use of direct, interaurally coordinated stimulation (e.g., Laback et al 2007;Litovsky et al 2010;Majdak et al 2006;van Hoesel 2007;van Hoesel et al 2009). CI listeners' sensitivity to ITD cues under more realistic conditions, i.e., with stimulation at multiple-electrode pairs, is a new and developing field of research with only a few studies published yet (e.g., Francart et al 2015;Ihlefeld et al 2014). In normal hearing, ITD sensitivity has been found to improve when the same ITD information is presented across different frequency bands compared to when the ITD is only presented in a single frequency channel (e.g., Buell and Hafter 1991;Buell and Trahiotis 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on ITD perception of amplitude-modulated, high-rate pulse trains when consistent ITD cues are presented at multiple-electrode pairs representing the location of a single sound source (Francart et al 2015;Ihlefeld et al 2014). Ihlefeld et al (2014) presented consistent ITD cues at two pitch-matched, interaural electrode pairs (i.e., a double pair) to investigate the combination of temporally interleaved envelope-ITD information across different stimulation sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation